Proteome dynamics of the cotyledonary haustorium and endosperm in the course of germination of Euterpe oleracea seeds. (September 2020) - Nascimento, José R.S.; Neto, Domingos F.; Coutinho, Ítalo C.; Domont, Gilberto B.; Nogueira, Fábio C.S.; Campos, Francisco A.P.
Highlights: 1965 proteins were identified in the cotiledonary haustorium and endosperm. The haustorium proteome is richer in hydrolases that the endosperm proteome. The diversity of hydrolases in the cotiledonary haustorium increases during germination. Abstract: The role of the cotyledonary haustorium (CH) in the mobilization of nutrient reserves in the endosperm of species of the palm family Arecaceae is a moot question. To shed light on this matter, we present here an analysis of the quantitative proteome changes associated with four developmental stages of CH and three of endosperm during germination. Together, a total of 1965 proteins were identified, being 1538 in the CH and 960 in the endosperm. Both in the CH and endosperm proteomes, we observed an increase in the diversity of hydrolases as the CH and endosperm develops. Qualitative proteomics analysis of four CH developmental stages indicated that each stage is populated by a unique set of proteins and the quantitative analysis showed an increase in the relative abundance of hydrolases, particularly mannan degrading enzymes, as development progresses. These results add weight to the hypothesis that the CH in the seeds of E. oleracea acts both as a conduit of carbon and nitrogen sources generated by the hydrolysis of the reserves in the endosperm and as a source of hydrolases that will contribute to the mobilization of these reserves.